Method Used to Study Passenger Traffic Flows at the Network-Wide and Regional Levels of the Railway Traffic Management Complex - E. A. Makarova; K. V. Surzhin; A. V. Sokolovskiy; S. B. Elizarov; A. G. Piunov (Вестник Научно-исследовательского института железнодорожного транспорта)
The paper tackles methodological approaches to determination of traffic demand development trends on the main routes of the JSC RZD network as well as principles of railway lines classification on the basis of long-distance traffic volume dynamics. The classification procedure employs algorithms of analytic passenger traffic flow investigations based on the up-to-date techniques of mathematical statistics and marketing analysis, as well as criteria and order of the JSC RZD network routes classification suppotring their prioritization in the context of infrastructure development. Long-distance passenger traffic volumes, forecasted continuity of traffic demand evolution, seasonal factors and competitiveness degree of passenger traffic flow routes were adopted as criteria of railway lines” multidimentional classification. Objects of classification involved in route formation are individual stations and groups of stations entering railway junctions, urban communities, constituent territories of the Russian Federation and individual railways as well as territorial station clusters entering megacities, resort areas and airport adjacent territories. Analytic base has been developed relying on collection and systematization of actual passenger traffic flow data of individual JSC RZD network routes for the years 2006 - 2014 and corresponding actual data related to competitive air transport. Methodical ware developed by the authors serves as analytic base, supporting rationalization processes dealing with the system of railway passenger services and generation of route network on the basis of actual passenger correspondences and long-term variation trends.